Synthetic displacement in the poetry of Al-Abbas bin Al-Ahnaf An analytical study - قدسي, نديم; يعقوب البيطار ,; تيسير جريكوس, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research studies the structural displacement in the poetry of Al-Abbas bin Al-Ahnaf in an analytical study, where the study begins with the concept of displacement, and the role of structural displacement in revealing the poetic position within the context, through two poetic issues, which are the introduction and the delay in the contexts of the actual sentence and the nominative sentence, and the attention that is manifested In the transition from one pronoun to another during speech, and their connection with the literary sense and artistic taste, through the movement that they perform within the poetic context, which leads to the disruption of the linguistic structure, and the opening of the semantic horizon to further spaces, and more expressive of the poet’s awareness of his world, and his belief in the necessity of the existing change. On demolition and rebuilding, through analyzing some poetic evidence in Al-Abbas's diwan, trying to trace the aesthetic impact of these two issues on the recipient, reflecting the goal that Al-Abbas wanted to deliver to him, which shows the extent of the depth of the effect of structural displacement on the meanings that the poet sought to put in front of him. the reader .